Utility of 3D multimodality imaging in the implantation of intracranial electrodes in epilepsy. (5th February 2015) - Nowell, Mark; Rodionov, Roman; Zombori, Gergely; Sparks, Rachel; Winston, Gavin; Kinghorn, Jane; Diehl, Beate; Wehner, Tim; Miserocchi, Anna; McEvoy, Andrew W.; Ourselin, Sebastien; Duncan, John
Summary: Objective: We present a single‐center prospective study, validating the use of 3D multimodality imaging (3DMMI) in patients undergoing intracranial electroencephalography (IC‐EEG). Methods: IC‐EEG implantation preparation entails first designing of the overall strategy of implantation (strategy) and second the precise details of implantation (planning). For each case, the multidisciplinary team made decisions on strategy and planning before the disclosure of multimodal brain imaging models. Any changes to decisions, following disclosure of the multimodal models, were recorded. Results: Disclosure of 3DMMI led to a change in strategy in 15 (34%) of 44 individuals. The changes included addition and subtraction of electrodes, addition of grids, and going directly to resection. For the detailed surgical planning, 3DMMI led to a change in 35 (81%) of 43 individuals. Twenty‐five (100%) of 25 patients undergoing stereo‐EEG (SEEG) underwent a change in electrode placement, with 158 (75%) of 212 electrode trajectories being altered. Significance: The use of 3DMMI makes substantial changes in clinical decision making.